2018
DOI: 10.14254/2071-789x.2018/11-2/4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Divisia Money on Monetary Model of Exchange Rate in Indonesia

Abstract: Stability of the exchange rate is critical for policy formulation in Indonesia and thus, has boosted the study of exchange rate behaviour. In this study, the monetary model of exchange rate has been utilised to determine the exchange rate for Indonesia. The model was improved by means of including the Divisia monetary aggregate as the money measure instead of conventional money supply. The ARDL approach, which was valid in spite of the variables' stationary properties, was used for the estimation. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
3
6
0
Order By: Relevance
“…This study has also conclusively shown that the monetary aggregate channel using Divisia mo ney is able to perform well in transmitting the impact of monetary policy. This is similar to the result presented by Leong et al (2018b) which stated that economic impact can be transmitted via monetary aggregate into output and inflation. Based on the empirical findings in this study, the monetary aggregate channel is dominant in Indonesia in both the short-and long-term.…”
Section: Discussionsupporting
confidence: 91%
“…This study has also conclusively shown that the monetary aggregate channel using Divisia mo ney is able to perform well in transmitting the impact of monetary policy. This is similar to the result presented by Leong et al (2018b) which stated that economic impact can be transmitted via monetary aggregate into output and inflation. Based on the empirical findings in this study, the monetary aggregate channel is dominant in Indonesia in both the short-and long-term.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the method is relatively simple to implement and is recommended for a small sample size (Ghatak & Siddiki, 2001;Narayan, 2005;Pesaran, Shin & Smith, 2001;Matar, 2016). Moreover, the variables are not restricted by a specific lag-length, which provides better results (Laurenceson & Chai, 2003;Leong et al, 2018).…”
Section: +α 2 Lm2 T +α 3 Infr T +α 4 Lipi T +α 5 Lppi T + α 6 Tb T +αmentioning
confidence: 99%
“…This procedure is still a pragmatic approach used for the estimation in various financial and economic studies (Waziri et al, 2018; Abaidoo, 2018; Okunade et al, 2018; Shakil et al, 2018). Monetary fundamentals also were found related to exchange rate using the ARDL in Indonesia (Leong et al, 2018) and thus the investigation is sensible for the Philippines.…”
Section: Introductionmentioning
confidence: 92%